Evaluation of Shatpada Fruit Fly Traps Versus Conventional Fruit Fly Traps in Citrus in India - Sandeep Singh; Srinivas Reddy; Ranjit Kadu; Y. V. Ingle; Sikha Deka; Raaj Kumar Kokoti; L. Ranjith Kumar; Aayush Kaushal; Deepa Bhagat; S. Priya Devi; Guranshpaul Singh; Ashok Kumar; et al. (Applied Fruit Science, 2026)

Structuring dry-fractionated faba bean protein concentrate using a micro-compounder: Effects of moisture, heat and salt addition - Andreas Hopf; Deepa Agarwal; Daniela Briceño Garcia; Peter Valtchev; Brent N. Kaiser; Roman Buckow; Fariba Dehghani (Journal of Food Engineering, 2026)

Morphological and simple sequence repeat (SSR)-based diversity of Capsicum germplasm characterizes population structure and enables marker-assisted selection for Phytophthora capsici resistance - Deepa Jaganathan; Jessica Michelle Gibbs; Noel Thomas; Theodore McAvoy; Mahnaz Azad; Miaoying Tian; Dennis N. Lozada; William Hendricks Railey; Amol N. Nankar (Euphytica, 2026)
Capsicum annuum is a globally important crop with rich genetic diversity that underpins breeding for productivity and disease resistance. In this study, we assessed 485 accessions representing a diverse Capsicum germplasm set, predominantly Capsicum annuum with a limited representation of related wild species using agro-morphological traits and simple sequence repeat markers to explore diversity, structure, and trait variation. Phenotypic evaluation of 352 accessions was conducted under field conditions during the 2024 summer season, where data were recorded on eight quantitative and four qualitative traits. Genetic characterization on the whole collection was performed using 24 polymorphic SSR markers selected for their known linkage to Phytophthora capsici resistance. A total of 308 alleles were detected post-binning, with an average of 12.83 alleles per locus and high polymorphism information content (mean PIC = 0.80). STRUCTURE analysis revealed three major genetic clusters (K = 3), supported by the Evanno ΔK method and consistent with clustering observed in Principal Component Analysis (PCA) and Neighbor-Joining (NJ). The clusters comprised predominantly C. annuum accessions, but also included individuals from C. baccatum , C. chinense , and other species, suggesting historical introgression and admixture. Phenotypic variation largely aligned with molecular groupings, supporting the complementary use of morphological and marker-based data. The high allelic diversity and defined population structure observed in this study provide a valuable foundation for genetic improvement, association mapping, and core collection development in Capsicum . In addition, the choice of Phytophthora -linked SSR markers provides an important platform for future association mapping and marker-assisted selection studies aimed at improving disease resistance in Capsicum . Graphical Abstract

Deacidification of vegetable oils: advanced technologies, mechanistic insights, and emerging strategies - G. Jeevarathinam; R. Rahul; J. Deepa; N. Sharath Kumar; C.S. Neethu; G. Sarojini; V. Siva Shankar; Punit Singh; Davinder Pal Singh Oberoi; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Chemistry, 2026)

Probiotic and Functional Attributes of Yeasts Isolated from Different Traditional Fermented Foods and Products - B. Shruthi; G. Adithi; N. Deepa; S. Divyashree; M. Y. Sreenivasa (Probiotics and Antimicrobial Proteins, 2025)

Spectroscopic Analysis of 4-MeO-TPA with Metal Oxide Nano-Assembly: Insights on Fluorescence Quenching and FRET - V. V. Koppal; R. Venkatesh; N. R. Banapurmath; Kalpana Sharma; Deepa H. K (Journal of Fluorescence, 2025)

Biological Decontamination of Mycotoxigenic Fusarium verticillioides Using Lactiplantibacillus plantarum MYSN128 Isolated from Traditional Vellappam: Implications for Food Safety and Global Mycotoxin Management - G. Adithi; Rakesh Somashekaraiah; B. Shruthi; S. Divyashree; N. Deepa; P. R. Vanitha; R. Vasundaradevi; B. V. Deepthi; M. Y. Sreenivasa (Current Microbiology, 2025)

Molecular Detection of Benzimidazole Resistance Associated with the F200Y Polymorphism in the β-Tubulin Gene of Ancylostoma caninum: First Report from India - Deepa Soman; R. Radhika; Bindu Lakshmanan; Asha Rajagopal; M. N. Priya; K. Syamala; Arun George (Acta Parasitologica, 2025)

Unique humoral immune response of pigs to repeated natural Japanese encephalitis virus infections: an amplifying host perspective - M. Dhanalakshmi; Himani Dhanze; Akash Mote; N. Narmatha; K. Sibi Thomas; R. Nithiaselvi; Deepa Mehta; M. Suman Kumar; K. N. Bhilegaonkar (Archives of Virology, 2025)

Bimetallic/Cellulose nanohybrids: A flexible, versatile, and sustainable biomaterial - Prajakta P. Baikar; Guruprasad R. Mavlankar; Deepa N. Rangadal; Minakshi N. Bhatu; Shubhangi P. Patil (Next Research, 2024)

Sero-epidemiology and risk factor investigation for exposure to Japanese encephalitis virus in swine populations reared in climatically diverse regions of India - Akash Balasaheb Mote; Balbir B. Singh; Deepa Mehta; Sagar M. Patel; M. Dhanalakshmi; M. Suman Kumar; K. N. Bhilegaonkar; Himani Dhanze (Tropical Animal Health and Production, 2024)

Fertile grounds: exploring male sterility in cotton and its marker development - V. Deepa Dharsini; A. Subramanian; N. Premalatha; N. Manikanda Boopathi; M. Djanaguiraman; V. P. Santhanakrishnan (Molecular Biology Reports, 2024)

Innovative agricultural diagnosis: DQRR-AFH algorithm model for effective leaf disease prevention and monitoring - S. L. Bharathi; N. Deepa; J. Sathya Priya; K. Muthulakshmi (Earth Science Informatics, 2024)

Evaluation of Limosilactobacillus fermentum MYSAGAM1 isolated from herbal Amla juice as a probiotic candidate with antifungal characteristics against Fusarium equiseti - G. Adithi; S. Divyashree; B. Shruthi; N. Deepa; M.Y. Sreenivasa (Food Bioscience, 2024)

Chemosensitizing potential of andrographolide in P-glycoprotein overexpressing multidrug-resistant cancer cell lines - Deepa Swati Lakra; Pradhapsingh B; Deepika N; Dhanalakshmi T; Kanimozhi G; Rajendra Prasad N (Natural Product Research, 2024)

Intracellular iron accumulation facilitates mycobacterial infection in old mouse macrophages - Stephen K. Kotey; Xuejuan Tan; Owen Fleming; Ramakrishnama Raju Kasiraju; Audrey L. Dagnell; Kyle N. Van Pelt; Janet Rogers; Steven D. Hartson; Nidheesh Thadathil; Ramasamy Selvarani; Rojina Ranjit; Sreemathi Logan; et al. (GeroScience, 2023)
Aging has a significant impact on the immune system, leading to a gradual decline in immune function and changes in the body’s ability to respond to bacterial infections. Non-tuberculous mycobacteria (NTM), also known as atypical mycobacteria or environmental mycobacteria, are commonly found in soil, water, and various environmental sources. While many NTM species are considered opportunistic pathogens, some can cause significant infections, particularly in individuals with compromised immune systems, such as older individuals. When mycobacteria enter the body, macrophages are among the first immune cells to encounter them and attempt to engulf mycobacteria through a process called phagocytosis. Some NTM species, including Mycobacterium avium ( M. avium ) can survive and replicate within macrophages. However, little is known about the interaction between NTM and macrophages in older individuals. In this study, we investigated the response of bone marrow–derived macrophage (BMMs) isolated from young (5 months) and old (25 months) mice to M. avium serotype 4, one of the main NTM species in patients with pulmonary NTM diseases. Our results demonstrated that BMMs from old mice have an increased level of intracellular iron and are more susceptible to M. avium serotype 4 infection compared to BMMs from young mice. The whole-cell proteomic analysis indicated a dysregulated expression of iron homeostasis–associated proteins in old BMMs regardless of mycobacterial infection. Deferoxamine, an iron chelator, significantly rescued mycobacterial killing and phagolysosome maturation in BMMs from old mice. Therefore, our data for the first time indicate that an intracellular iron accumulation improves NTM survival within macrophages from old mice and suggest a potential application of iron-chelating drugs as a host-directed therapy for pulmonary NTM infection in older individuals.

Inferring ecological strategies of Psenopsis spp. (Teleostei: Centrolophidae) inhabiting Indian waters from morphological features - K. V. Aneesh Kumar; M. P. Rajeeshkumar; M. Hashim; K. P. Deepa; J. L. Otero-Ferrer; N. Saravanane; Sujitha Thomas; K. K. Bineesh; V. M. Tuset (Marine Biology Research, 2022)

Near reef abundance and on–offshore distribution of tuna larvae around Minicoy Island in Lakshadweep Sea, India - K. V. Aneesh Kumar; K. P. Deepa; M. M. Muhammed Rafeeq; G. Sree Renjima; Hashim Manjebrayakath; B. R. Smitha; N. Saravanane; M. P. Prabhakaran; V. N. Sanjeevan; M. Sudhakar (Marine Biology Research, 2020)

Synthesis of magnetic carbon nanocomposites by hydrothermal carbonization and pyrolysis - M. T. H. Siddiqui; Sabzoi Nizamuddin; Humair Ahmed Baloch; N. M. Mubarak; Deepa K. Dumbre; Inamuddin; Abdullah M. Asiri; A. W. Bhutto; Madapusi Srinivasan; G. J. Griffin (Environmental Chemistry Letters, 2018)

Occurrence of a rare gigantic sized deep-sea cod Lepidion inosimae (Günther, 1887) in the Northwestern Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2017)

High-density lipoprotein from subjects with coronary artery disease promotes macrophage foam cell formation: role of scavenger receptor CD36 and ERK/MAPK signaling - S. Sini; D. Deepa; S. Harikrishnan; N. Jayakumari (Molecular and Cellular Biochemistry, 2017)

First record of deep-sea gigantic pycnogonid Colossendeis colossea Wilson, 1881 from the Western Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2016)

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Loss of P2Y2 Nucleotide Receptors Enhances Early Pathology in the TgCRND8 Mouse Model of Alzheimer's Disease - Deepa Ajit; Lucas T. Woods; Jean M. Camden; Christina N. Thebeau; Farid G. El-Sayed; Glen W. Greeson; Laurie Erb; Michael J. Petris; Douglas C. Miller; Grace Y. Sun; Gary A. Weisman (Molecular Neurobiology, 2014)

Genetic dissection of drought tolerance in chickpea (Cicer arietinum L.) - Rajeev K. Varshney; Mahendar Thudi; Spurthi N. Nayak; Pooran M. Gaur; Junichi Kashiwagi; Lakshmanan Krishnamurthy; Deepa Jaganathan; Jahnavi Koppolu; Abhishek Bohra; Shailesh Tripathi; Abhishek Rathore; Aravind K. Jukanti; et al. (Theoretical and Applied Genetics, 2014)

Looking different, feeling different: women’s reactions to risk-reducing breast and ovarian surgery - Nina Hallowell; Brandi Baylock; Louise Heiniger; Phyllis N. Butow; Deepa Patel; Bettina Meiser; Christobel Saunders; Melanie A. Price (Familial Cancer, 2012)

Persistence and Dissipation of Fluopicolide in/on Grape Berries and Soil Under Semi Arid Tropical Climatic Conditions of India - Soudamini Mohapatra; A. K. Ahuja; M. Deepa; G. K. Jagdish; N. Rashmi; Sampath Kumar; G. S. Prakash (Bulletin of Environmental Contamination and Toxicology, 2011)

Persistence and Dissipation of Flubendiamide and Des-iodo Flubendiamide in Cabbage (Brassica oleracea Linne) and Soil - Soudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagadish; N. Rashmi (Bulletin of Environmental Contamination and Toxicology, 2010)

Fate of Fipronil and its Metabolites in/on Grape Leaves, Berries and Soil Under Semi Arid Tropical Climatic Conditions - Soudamini Mohapatra; M. Deepa; G. K. Jagdish; N. Rashmi; Sampath Kumar; G. S. Prakash (Bulletin of Environmental Contamination and Toxicology, 2010)

Antifungal activity of Datura stramonium, Calotropis gigantea and Azadirachta indica against Fusarium mangiferae and floral malformation in mango - K. Usha; B. Singh; P. Praseetha; N. Deepa; D. K. Agarwal; R. Agarwal; A. Nagaraja (European Journal of Plant Pathology, 2009)